Teaching Games for Understanding in basketball camp: the impact on process and product performance. [Teaching Games for Understanding en un campamento de baloncesto: impacto en el rendimiento del proceso y del producto]. - Mariana Calábria-Lopes; Pablo Juan Greco; Juan Carlos Pérez-Morales (Revista Internacional de Ciencias del Deporte, 2019)
The purposes of the current study were to verify the correlation between product and process performance of basketball passing and shooting skills and to examine the effects of TGfU intervention in a basketball camp format on process and product performance of these skills in children. Participants included 18 novices (age: M = 10.89, SD = 1.02 years old) in basketball. They participated in 22.5 hours of TGfU training over five consecutive days and completed pre and post assessments. Data were collected using process and product assessments, and a declarative knowledge questionnaire. Results showed no correlation between the dependent variables. Significant differences between pre- and posttest were found only for process performance of passes, product performance of shooting in game context, and declarative knowledge of both skills. No differences were found for product-oriented assessment of shooting and passing isolated skills. Therefore, it was possible to conclude that the use of process and product assessments to evaluate sport-specific skills after a TGfU intervention in a basketball camp may provide different and complementary information about performance levels in teaching – learning process.